Assessment of grain boundary cohesion of technically pure and boron micro-doped molybdenum via meso-scale three-point-bending experiments. (September 2021) - Jakob, S.; Hohenwarter, A.; Lorich, A.; Knabl, W.; Pippan, R.; Clemens, H.; Maier-Kiener, V.
Graphical abstract: Highlights: The GB crack length was measured on the tension-loaded sample surface. B doping enhances the cohesion, resulting in lower relative length of separated GBs. GB separations were analyzed regarding misorientation and potential slip transfer. This characterization method enables fast and simple testing of GB engineering concepts. Abstract: Grain boundary engineering plays a major role for controlling the properties of modern high-performance materials. Especially Mo and its alloys have advantageous high-temperature structural properties as well as a number of attractive functional properties. However, depending on the processing state, technically pure Mo is prone to intercrystalline failure at low temperatures. The addition of B and/or C is known to improve interface cohesion, allowing for a targeted improvement of mechanical properties through segregation engineering. In this work, the early stages of crack initiation of technically pure and B micro-doped Mo are investigated by scanning electron microscopy on the tension-loaded surface after three-point-bending of mm-sized specimens. Increased grain boundary cohesion is evident from a drastically reduced relative length of separated interfaces in the B-doped material. The presence of B at the grain boundaries is confirmed via atom probe tomography experiments.